The Effect Of Green Transformation Leadership On Government Performance Accountability: Through Organizational Learning - Imam, Sabferrial Fernando; Astini, Rina (International Journal of Law Policy and Governance, 2022)
This study aims to analyze quantitatively related to the factors driving the accountability of the performance of government agencies. This study examines the effect of green transformational leadership and organizational learning on government performance accountability. The survey method approach uses a questionnaire to answer research questions. Hypothesis testing using Structural Equation Modelling - Partial Least Square (SEM-PLS). Analysis of research data involved 100 respondents consisting of officials and staff at the Banten Provincial Government. The results of the study state that green transformational leadership and organizational learning have a positive effect on the performance accountability of government agencies. It was concluded that, the role and influence of a leader in the organization in stages. This is because leadership makes a major contribution to the accountability of the performance of government agencies. While the importance of learning in organizations can have a big impact and influence in improving the quality of accountability for the performance of government agencies, especially local governments.